Acceptance of a Symptom-Based Approach for COVID-19 rtRT-PCR Testing to Conserve Resources in a Lower Middle-Income Setting - S. M. Rashed Ul Islam; Tahmina Akther; Md. Abdullah Omar Nasif; Sharmin Sultana; Saif Ullah Munshi (SAGE Publishing, 2021)
SARS-CoV-2 initially emerged in Wuhan, China in late 2019. It has since been recognized as a pandemic and has led to great social and economic disruption globally. The Reverse Transcriptase Real-Time Polymerase Chain Reaction (rtRT-PCR) has become the primary method for COVID-19 testing worldwide. The method requires a specialized laboratory set up. Long-term persistence of SARS-CoV-2 RNA in nasopharyngeal secretion after full clinical recovery of the patient is regularly observed nowadays. This forces the patients to spend a longer period in isolation and test repeatedly to obtain evidence of viral clearance. Repeated COVID-19 testing in asymptomatic or mildly symptomatic cases often leads to extra workload for laboratories that are already struggling with a high specimen turnover. Here, we present 5 purposively selected cases with different patterns of clinical presentations in which nasopharyngeal shedding of SARS-CoV-2 RNA was observed in patients for a long time. From these case studies, we emphasized the adoption of a symptom-based approach for discontinuing transmission-based precautions over a test-based strategy to reduce the time spent by asymptomatic and mildly symptomatic COVID-19 patients in isolation. A symptom-based approach will also help reduce laboratory burden for COVID-19 testing as well as conserve valuable resources and supplies utilized for rtRT-PCR testing in an emerging lower-middle-income setting. Most importantly, it will also make room for critically ill COVID-19 patients to visit or avail COVID-19 testing at their convenience.